Status of Enhancing Learners’ Higher Order Thinking Skills in the Teaching of Reading Skills at Ethiopian Higher Education: Analyzing Reading Exercises and Learners’ Perceptions - Sintayehu Gebremariam Gergera (Universitas Galuh, 2023)
Abstract In the twenty-first century, the broad availability of information and technological innovation has resulted in a paradigm shift in the goal of education. As a result, in order to produce engaged citizens capable of facing the demands and obstacles of the century, boosting learners' higher cognitive skills has become a priority in modern education. Language teachers' responsibilities in modern language teaching have expanded to include improving students' thinking skills. In line with this idea, this study was aimed at examining the role teaching reading skills at a higher education institution has in enhancing learners’ higher-order thinking skills. In order to achieve the main objective of the study, an analysis was carried out on the levels of thinking that questions in reading exercises aim to elicit from the learners and how the students perceive the reading exercises from the perspective of enhancing higher-order thinking skills. The findings of the study show that the reading exercises are dominated by lower-order questions; there are fewer higher-order questions in the exercises. Thus, the reading exercises are not capable of enhancing learners’ higher-order thinking skills. The students also have the perception that the reading exercises are not meant to develop their higher-order thinking skills. There is no statistically significant difference between male and female participant students among their perceptions identified in the study.